Secondary metabolites from Sarcosperma kontumense - Vuong, Nguyen Quoc; Hue, Nguyen Thi; Hang, Pham Thi; Nam, Nguyen Hoang; Tuan, Nguyen Le; Thanh, Le Nguyen; Cuong, Pham Van; Yen, Duong Hai; Nhiem, Nguyen Xuan; Tai, Bui Huu; Kiem, Phan Van (Vietnam Journal of Science and Technology, 2023)
Six urs-ketone triterpenes (1 - 6) and two flavonoids (7, 8) from the leaves of Sarcosperma kontumense Gagnep. ex Aubrév., were isolated. Their chemical structures were elucidated as 2α,3α,19α,23-tetrahydroxy-13,27-cyclours-11-en-28-oic acid (1), rotundic acid (2), euscaphic acid (3), ursolic acid (4), pomolic acid (5), jacoumaric acid (6), (+)-catechin (7), and (-)-epi-catechin (8), by spectroscopic analyses including ESI-MS, 1D and 2D NMR spectra and comparison with those reported in the literatures. In which, compounds 1, 2, 4, 6, and 8 were firstly isolated from the genus Sarcosperma.